English Language Policy in Relation to Teachers and Teacher Educators in Latvia: Insights from Activity Systems Analysis - Bicjutko, Tatjana; Goba-Medne, Līva (Acta Paedagogica Vilnensia, 2020)
The ambitious objectives of European language policy and the strive for competitiveness have led to an increasing emphasis on foreign language competence at the level of national education systems. Using Spolsky’s onion model of language policy (2004) and Engeström’s Expansive Learning theory (1987, 2008), the study attempts to determine the formative influence of the existing multilayered language policy on the professional development of Latvian educators with the aim to compare the situation for teachers and teacher educators in respect of their English language proficiency. Given the prioritisation of English and strategic differences in foreign language management in relation to teachers and faculty, the activity systems analysis points to significantly higher demands and concomitant pressure in respect of English language competence of academic staff, and the lack of incentives to increase their proficiency for teachers. Remedying the existing situation through policy making, both systemic and individual perspectives should be taken into account, as their interplay affects the agency of educators in achieving the goals.